(3aJhM GdZjH aj GdcTa Yf bfGY GdQjH (B:s (3hgh MGTjI GdWjHj Ydi GdcTGa (B/s - (3GdWjHj, GdMSjf Hf eMeO Hf YHO Gddg,s (3Jhaj (B743 (3gLQjG(B.s; (3GdZhL , EjGOs; (3YWG , Lejds ((3OHj (B:s (3LGFRI OHj GdOhdjI ddbQGf GdcQje ,s, 2013)
(3JHOC ef Chd GdbQBf Edi GdBjI Qbe (B19 (3ef ShQI GdESQGA(B.s
(3fSNI hGVMI GdJUhjQ(B.s
(3Chdg (B: (3HYO GdHSedI GdMeO ddg GdPj CfRd Ydi YHOg GdcJGH hde jLYd dg YhLG hLYdg bjeG dEbGeI (B... (3Phj GdCdHGH adG fQi ajg YhLG (B...s
(3BNQg fGbU hjfJgj H` (B: ... (3Cj COQc eG SYi aj (B... (3hNU GdeSYGI HWdH GdecQeI hGdSYGjI CNP GdUObI hHcSH GdecGJH dYJb QbHJg (B...s
(3GdCOGI GdJhKjbjI (B: (3GdeOGNd, U(B. 328-(3GdCYdGe, eL(B. 2(3, U(B. 256-(3cTa GdXfhf, eL(B. 2(3, U(B. 1240-(3gOjI GdYGQajf, eL(B. 1(3, U(B. 285.s
(3ejcQhajde(B.s
(3ecJHI YGWa CafOj ;s
Keywords: (3GdbQBfs -- (3JaGSjQ dZhjIs -- (3eNWhWGJs